An agent based simulation of COVID-19 history in Catalonia using extensive real datasets - M. Bosman; Y. Cordon; M. Duran-Sala; L. Gabbanelli; C. García-Pérez; X. Jordan; M. Manera; P. Masjuan; A. Medina; Ll. M. Mir; A. Oròs; V. Vitagliano (Scientific Reports)
Abstract During the COVID-19 pandemic, effective public policy interventions have been crucial in combating virus transmission, sparking extensive debate on crisis management strategies and emphasizing the necessity for reliable models to inform governmental decisions, particularly at the local level. Leveraging disaggregated socio-demographic microdata, including social determinants, age-specific strata, and mobility patterns, we design a comprehensive network model of Catalonia’s population and, through numerical simulation, assess its response to the outbreak of COVID-19 over the two-year period 2020–21. Our findings underscore the critical importance of timely implementation of broad non-pharmaceutical measures and effective vaccination campaigns in curbing virus spread; in addition, the identification of high-risk groups and their corresponding maps of connections within the network paves the way for tailored and more impactful interventions.